A call to action: strong long-term limnological changes in the two largest Ethiopian Rift Valley lakes, Abaya and Chamo. Issue 2 (3rd April 2017) - Teffera, Fassil E.; Lemmens, Pieter; Deriemaecker, Arne; Brendonck, Luc; Dondeyne, Stefaan; Deckers, Jozef; Bauer, Hans; Gamo, Feleke W.; De Meester, Luc
Abstract: The 2 largest Ethiopian Rift Valley lakes, Abaya and Chamo, are dominant socioecological systems with important potential for ecotourism because of their attractive setting with Nechisar National Park. We report on changes in water quality in these lakes during recent decades. We integrated data on key limnological variables during the last 55 years by supplementing historical literature data with our own field measurements. Our analyses provide strong evidence for a steady increase in nutrient concentrations and decrease in water transparency. Total phosphorus and total nitrogen concentrations in both lakes over the study period increased 5- and 7-fold, respectively. Similarly, water transparency decreased, especially in Lake Chamo, which used to have clear water but is now becoming a sediment-loaded lake similar to Lake Abaya. We reconstructed fertilizer use and land use changes in the region during the past decades. The combined data suggest that the dramatic eutrophication we observed in the lakes is likely associated with increased fertilizer use or other activities related to intensified agricultural practices, and the decline in water transparency is probably associated with low tree cover due to deforestation. The profound changes in the ecology of both lakes may jeopardize the delivery of ecosystem services in the region, including water supply, fisheries, and ecotourism. Our results stress the urgent need for measures that prevent further environmental deterioration of the unique heritage provided by the Ethiopian Rift Valley lakes.